Cut in Stone: Confederate Monuments and Theological Disruption - Newson, Ryan Andrew (Baylor University Press, 2020)
Intro -- Contents -- List of Images -- Preface -- Introduction -- 1 History: Monuments' Shifting Contexts -- 2 Past: Memories Constructed -- 3 Future: Whiteness Concretized -- 4 Present: Wounds Obscured -- 5 Apocalypse: Disrupting Palliative Monuments -- Notes -- Bibliography -- Index.